Current State of Circulating MicroRNAs as Cancer Biomarkers. (6th January 2020) - He, Yuqing; Lin, Juanjuan; Kong, Danli; Huang, Mingyuan; Xu, Chengkai; Kim, Taek-Kyun; Etheridge, Alton; Luo, Yanhong; Ding, Yuanlin; Wang, Kai
Abstract: BACKGROUND: Numerous studies have demonstrated the existence of stable regulatory RNAs, microRNAs (miRNAs), in the circulation and have shown that the spectrum of these extracellular miRNAs is affected by various pathologic conditions including cancers. CONTENT: Circulating miRNAs have been the focus of numerous cancer biomarker discovery efforts over the past few years; however, a considerable number of these studies have yielded inconsistent and irreproducible findings. Here, we have summarized and compared the results of studies covering 8 different cancer types to address key questions, including the possibility of using circulating miRNA to detect cancers and what factors may affect miRNA signatures. Although identifying circulating miRNA signatures to detect specific types of early stage cancers can be challenging, study results suggest that it may be possible to use miRNAs to detect cancers in general. SUMMARY: Circulating miRNA is a rich source for potential disease biomarkers; however, factors, both intrinsic and extrinsic, that may affect measurement of circulating miRNA have not been fully characterized. Better understanding of intra- and intercellular miRNA trafficking and the fundamental biology of cancer cell–derived lipid vesicles may facilitate the development of circulating miRNA-based biomarkers for cancer detection and classification.